Ragionevolezza della fede. Rapporto tra fede e ragione in Tommaso d’Aquino - Michał Oleksowicz (Scientia et Fides, 2015)
Rationality of faith. Relationship between faith and reason in Thomas Aquinas The rationality of the Christian faith has been an issue debated for centuries. The relationship between faith and reason is an intrinsic reality of Christian thought. But on the other hand from the beginning the Christianity it was a form of religion based on the assent of faith and not on a human justification. Here comes the heart of the problem in the relationship between Christian faith and reason, because the object of faith is not obvious. Instead, in general terms the rational knowledge is based on evidence and the principles of logic. But the act of faith, as evidenced by St. Thomas, is something more than the simple rationality: “act of the intellect gives assent to the divine truth under the influence of the will moved by God’s grace”. It is intended to demonstrate, on the basis of the thought of St. Thomas, that his position clearly can be considered as an attempt to achieve a balance covering the relationship between faith and reason. On the one hand, faith does not fall into irrationality of fideism. On the other hand, the faith in the thomistic conception has not been reduced to a form of rationalism. An attempt to read again the thomistic thought can be very fruitful to promote a dialogue between faith and reason.